Putting music to trial: Consensus on key methodological challenges investigating music‐based rehabilitation. Issue 1 (30th September 2022) - Grau‐Sánchez, Jennifer; Jamey, Kevin; Paraskevopoulos, Evangelos; Dalla Bella, Simone; Gold, Christian; Schlaug, Gottfried; Belleville, Sylvie; Rodríguez‐Fornells, Antoni; Hackney, Madeleine E.; Särkämö, Teppo
Abstract: Major advances in music neuroscience have fueled a growing interest in music‐based neurological rehabilitation among researchers and clinicians. Musical activities are excellently suited to be adapted for clinical practice because of their multisensory nature, their demands on cognitive, language, and motor functions, and music's ability to induce emotions and regulate mood. However, the overall quality of music‐based rehabilitation research remains low to moderate for most populations and outcomes. In this consensus article, expert panelists who participated in the Neuroscience and Music VII conference in June 2021 address methodological challenges relevant to music‐based rehabilitation research. The article aims to provide guidance on challenges related to treatment, outcomes, research designs, and implementation in music‐based rehabilitation research. The article addresses how to define music‐based rehabilitation, select appropriate control interventions and outcomes, incorporate technology, and consider individual differences, among other challenges. The article highlights the value of the framework for the development and evaluation of complex interventions for music‐based rehabilitation research and the need for stronger methodological rigor to allow the widespread implementation of music‐based rehabilitation into regular clinical practice.